ANALISIS KESULITAN BELAJAR SISWA KELAS XII IPA SMA NEGERI 3 PONTIANAK PADA MATERI REPRODUKSI SEL - Budiman, Muhammad Sholid; Candramila, Wolly; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe abundance of elusive concepts that are abstract and cannot be observed directly can cause learning difficulties to the students. This research aimed to know the percentage of student learning difficulties per learning objective and factors that cause student learning difficulties in cell reproduction material. The research method used was descriptive research with qualitative strategy in the form of case study. The research subjects were 37 students of class XII IPA 3 Academic Year 2016/2017 in SMA Negeri 3 Pontianak. The research instruments used were a diagnostic test sheet consisted of 20 questions and a questionnaire equipped with interviews to know the factors causing student learning difficulties on cell reproduction material. The result of the research showed that the percentage of student learning difficulties in the cell reproduction material was 79.3% or in high category. Factors that caused student learning difficulties in cell reproduction material consisted of two, namely internal and external factors. In general, internal factors (62.24%) contributed more than external factors (55.29%). Keywords: Percentage of Learning Difficulties, Cell Reproduction Material, Factors Causing Learning Difficulties.